Kajian Kapasitas Paru Pekerja yang Berobat di Klinik Pabrik Semen Bosowa Maros Tahun 2020 - Rana, Angeline; Nurliana, Nurliana; Naiem, M Furqaan (Fakultas Kedokteran Universitas Bosowa, 2023)
The cement industry is one of the industries that produces adhesive materials or aggregates as a form in the infrastructure development process and the country's economic development. One of the negative impacts of the cement industry is air pollution by dust which can directly affect lung capacity and physiology which involves the immune factor in a person. Assessment of dust exposure in humans needs to consider, among others, the source of exposure/type of factory, duration of exposure, exposure from other sources, physical activity and potential concomitant factors such as age, gender, ethnicity, smoking habits, and allergen factors. The aim of the study was to determine the distribution of lung capacity studies in workers based on (1) age (2) gender (3) work units (4) length of exposure (5) years of service. This research was conducted on 372 workers who were seeking treatment at the Bosowa Maros cement factory clinic in 2020. This research used an observational method with a descriptive approach using secondary data in the form of workers' medical checkups in the form of spirometry examinations at the Bosowa Maros Cement Factory Clinic. Data analysis was processed using SPSS software. The results of this study show the distribution of lung capacity studies in workers at the Bosowa Maros Cement Factory Clinic in 2020, namely: (1) age at risk 18-25 years (100%), (2) gender at risk is more in women (2.5%), (3) the quarry work unit has more risk (62.7%), (4) the longer the risk exposure is < 8 hours/day (100%), (5) the longer the work period the risk is more > 26 – 31 years (6.6%). The conclusion of the study is that the lung capacity of workers who are most at risk is in the age group of 18-25 years, female sex, quarry work unit, length of exposure < 8 hours/day and working period > 26-31 years.